GOLD INVESTMENT BY INSTALLMENT IN THE BANK INDONESIAN SHARIA KABANJAHE BRANCH: Analysis of Law No. 21 of 2008 and DSN MUI Fatwa Number 77 of 2010 - Wahyudi Ganda Syahputra; Sri Sudiarti; Hafsah Hafsah (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2021)
Bank Syariah Indonesia Gold Installment products, are in great demand by Bank Syariah Indonesia customers, including those in Kabanjahe, Karo-North Sumatra. This study examines the practice of investing in gold installments that have been regulated in Law No. 21 of 2008 and legitimized by the DSN fatwa of the Indonesian Ulema Council No. 77/DSN/MUI/VI/2020, whose legality is still being debated in Islamic law. The type of research used is field qualitative with a statutory approach and a case approach. The study results show that applying gold installment investments at BSI Kabanjahe complies with the provisions stipulated in Law No. 21 of 2008 concerning Islamic banking. Buying and selling gold in cash, either through ordinary buying and selling or buying and selling murabaha in the perspective of the DSN MUI fatwa Number 77 of 2010, is legally permissible (mubah or ja'iz). Then the solution to the obstacles in implementing gold installment investments at Bank Syariah Indonesia Kabanjahe Branch is to increase promotion and understanding to the public about gold investment products and discipline customers who are disobedient in paying by giving warning letters.Produk Cicil Emas Bank Syariah Indonesia sangat diminati oleh nasabah Bank Syariah Indonesia, termasuk di Kabanjahe, Karo-Sumatera Utara. Penelitian ini mengkaji praktek investasi cicilan emas yang telah diatur dalam UU No. 21 tahun 2008 dan dilegitimasi oleh fatwa DSN Majelis Ulama Indonesia No. 77/DSN/MUI/VI/2020, yang notabene masih diperdebatkan legalitasnya dalam syariat Islam. Jenis penelitian yang digunakan adalah kualitatif lapangan dengan pendekatan perundang-undangan dan pendekatan kasus. Hasil penelitian menunjukkan bahwa penerapan investasi cicilan emas di BSI Kabanjahe telah sesuai dengan ketentuan yang diatur dalam Undang-undang No. 21 tahun 2008 tentang perbankan syariah. Jual beli emas secara tidak tunai, baik melalui jual beli biasa atau jual beli murabahah dalam perspektif fatwa DSN MUI Nomor 77 tahun 2010 adalah hukumnya boleh (mubah atau ja’iz). Kemudian solusi terhadap kendala dalam pelaksanaan investasi cicilan emas di Bank Syariah  Indonesia Cabang Kabanjahe yaitu memperbanyak promosi dan pemahaman kepada masyarakat tentang produk investasi emas serta menertibkan nasabah yang tidak taat membayar dengan pemberian surat peringatan